The effect of concentrate feeding strategies on rumen parameters, milk production and milk composition of Jersey cows grazing ryegrass (Lolium multiflorum) or kikuyu (Pennisetum clandestinum) pasture - Joubert, Matthys Du Toit (Stellenbosch : Stellenbosch University., 2012)
Thesis (MScAgric)--Stellenbosch University, 2012